Escherichia coli lipopolysaccharides diminish and enhance cell function of human polymorphonuclear leukocytes. - Henricks, P A (1983)
The effects of the lipopolysaccharide (LPS) of Escherichia coli J5 and 0111B4 on the function of human polymorphonuclear leukocytes (PMN) were tested. E. coli J5 is a UDP-galactose-4-epimerase-deficient mutant of E. coli 0111B4, and its LPS, therefore, contains mainly lipid A, as it lacks the polysaccharide side chains. PMN which had been incubated with J5 LPS showed decreased phagocytic, chemotactic, and metabolic activities as compared with control PMN. In contrast, incubation of PMN with 0111B4 LPS had no effect or even an enhancing effect on PMN function. When lipid A and the polysaccharide fraction were isolated from 0111B4 LPS, it was shown that lipid A had the same deleterious effect on PMN function as did J5 LPS and that the LPS fraction had no effect. When PMN were incubated with J5 LPS or lipid A, it could be shown that these structures were able to induce PMN to generate superoxide and chemiluminescence. 0111B4 LPS and the polysaccharide component were able to generate a metabolic burst by the PMN to a lesser extent. The induced defects in PMN function by J5 LPS could be prevented when polymyxin B or an oxygen-radical scavenger was present. We hypothesize that the lipid A portion of LPS is toxic for PMN due to the induction of toxic oxygen species by the PMN. These toxic oxygen species destroy the phagocytic, chemotactic, and metabolic activities of the PMN.